Implementasi NodeMCU ESP8266 dan Sensor Cahaya Pada Lampu Berbasis Internet Of Things - Rahmat Irsyada; Muhdlor Auhal Haq; Naila Afina Rohmah; Prima Angga Hadi Saputra; Roikhatul Jannah (Jurnal ilmiah Sistem Informasi dan Ilmu Komputer, 2022)
The conventional use of led lights (Light Emitting Diode) is still considered inefficient in its control. Utilizing technology in the field of the Internet of Things greatly helps the efficiency of time and movement in controlling lights in real time or real through connected internet networks. In previous research, an automatic light switch and home temperature monitoring using VB. Net and Arduino. In this research, the lights will be integrated into the Internet of Things using NodeMCU ESP8266 and ldr (Light Dependent Resistor) sensors to detect incoming light and can be controlled through the Blynk application. This research is designed using SDLC (System Development Life Cycle) method of waterfall model and Arduino IDE as text editor application to write and upload code to NodeMCU ESP8266. The result of this research, the lamp can be controlled through the Blynk application, when the button is turned on and off the lamp acts on or off and the lamp can react on and off when it reaches a certain incoming light indicator on the LDR (Light Dependent Resistor) sensor.